The Basic Shot Put Skills Improvement through Modification of Plastic Ball Media in Elementary School - Aryo Bayu Allubsy; Bambang Suharyono (Media Ilmu Keolahragaan Indonesia, 2023)
Abstract. Based on the reality conditions, the fifth grade students at Tunglur Public Elementary School, Badas District, Kediri Regency, experienced difficulties when lifting and throwing iron balls in shot put movements. Minimal strength in lifting and throwing iron balls resulted in errors of the basic shot put movement, therefore a modification of learning media was needed. The research method used was Classroom Action Research (CAR) which was conducted through several steps, namely planning (Plan), Implementation (Action), Observation (Observe), and reflection (Reflect). The stages of the research included pre-cycle, cycle 1 and cycle 2. The pre-cycle was conducted to observe the constraints in shot put learning. In the results of cycle 1 that the total scores of very good and good overall students were 47%, which indicated that the research was not successful. Then cycle 2 was conducted with the results of the total acquisition scores of very good and good overall students were 64%, which indicated that the research was successful. So it can be concluded that the application of media modification in the form of plastic balls in shot put learning can improve the basic ability of shot put in fifth grade students of Tunglur Public Elementary School, Badas District, Kediri Regency.Abstract in Indonesia. Berdasarkan kondisi realita pada siswa kelas V SD Negeri Tunglur Kecamatan Badas Kabupaten Kediri, mengalami kesulitan saat mengangkat dan melempar bola besi daam gerakan tolak peluru. Kekuatan yang minim dalam mengangkat serta melempar bola besi mengakibatkan kesalahan dalam gerakan dasar tolak peluru, sehingga diperlukan modifikasi media pembelajaran. Metode penelitian yang digunakan ialah Penelitian Tindakan Kelas (PTK) yang dilakukan melalui beberapa langkah yaitu perencanaan (Plan), Pelaksanaan (action), Pengamatan (observe), dan refleksi (reflect). Tahapan penelitian antara lain pra siklus, siklus 1 dan siklus 2. Pra siklus dilakukan untuk mengamati kendala dalam pembelajaran tolak peluru. pada hasil siklus 1 bahwa jumlah perolehan nilai sangat baik dan baik keseluruhan siswa sebesar 47%, yang artinya penelitian belum berhasil. Maka dilakukan siklus 2 dengan hasil jumlah perolehan nilai sangat baik dan baik keseluruhan siswa sebesar 64%, yang artinya penelitian berhasil. Maka dapat disimpulkan bahwa penerapan modifikasi media berupa bola plastik pada pembelajaran tolak peluru dapat meningkatkan kemampuan dasar tolak peluru pada siswa kelas V SD Negeri Tunglur Kecamatan Badas Kabupaten Kediri.